2014
DOI: 10.1186/s12870-014-0358-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of carbohydrate metabolism during bulblet formation and development in Lilium davidii var. unicolor

Abstract: BackgroundThe formation and development of bulblets are crucial to the Lilium genus since these processes are closely related to carbohydrate metabolism, especially to starch and sucrose metabolism. However, little is known about the transcriptional regulation of both processes. To gain insight into carbohydrate-related genes involved in bulblet formation and development, we conducted comparative transcriptome profiling of Lilium davidii var. unicolor bulblets at 0 d, 15 d (bulblets emerged) and 35 d (bulblets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 41 publications
5
123
0
Order By: Relevance
“…28) In this study, starch and sucrose contents were determined during the preparation of regenerated bulblets in vitro. Results indicate that starch content in mother scales and bulblets stabilized after 45 d, after which bulblets developed with a final and complete shape.…”
Section: Discussionmentioning
confidence: 99%
“…28) In this study, starch and sucrose contents were determined during the preparation of regenerated bulblets in vitro. Results indicate that starch content in mother scales and bulblets stabilized after 45 d, after which bulblets developed with a final and complete shape.…”
Section: Discussionmentioning
confidence: 99%
“…Lily bulbs are good sources of starches, and its content accounted for 62.33% to 69.07% of the dry weight (Yu, Zhang, Li, Wang, & Xiong, 2015). The starch physicochemical properties, including morphology, amylose, crystal, and thermal properties, were affected by growth periods and cultivars (Li, Gao, Jiang, & Xia, 2012;Li et al, 2014;Takeda, Takeda, & Hizukuri, 1983;Wu, Wu, Jiao, Zhang, & Lv, 2012;Yu, Zhang, Shao, et al, 2015). Huang et al (2017) found that UV-C treatment downregulated the activities of α-amylase and β-amylase resulting in a higher content than that of the control during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analyses have been performed in several Lilium species, to explore the effect of cold exposure (Wang et al ., ; Villacorta‐Martin et al ., ), carbohydrate metabolism (Li et al ., ), stress (Wang et al ., ), and dormancy release (Wang et al ., ). To the best of our knowledge, no transcriptome analysis was ever performed in the context of bulb size.…”
Section: Introductionmentioning
confidence: 99%